Patient-reported treatment satisfaction and choice of dosing frequency with biologic treatment for moderate to severe plaque psoriasis - Zhang M; Brenneman SK; Carter CT; Essoi BL; Farahi K; Johnson MP; Lee S; Olson WH (Patient Preference and Adherence, 2015)
Mingliang Zhang,1 Susan K Brenneman,2 Chureen T Carter,1 Breanna L Essoi,2 Kamyar Farahi,1 Michael P Johnson,2 Seina Lee,1 William H Olson3 1Health Economics and Outcomes Research, Janssen Scientific Affairs, LLC, Horsham, PA, 2Health Economics and Outcomes Research, Optum Life Sciences, Eden Prairie, MN, 3Research and Analysis Strategy, Janssen Scientific Affairs, LLC, Titusville, NJ, USA Background: Moderate to severe plaque psoriasis has a serious effect on health-related quality of life. Patients treated with biologic medications place importance on satisfaction and treatment frequency options. We assessed patient-reported treatment satisfaction and dosing frequency choice with biologics.Methods: We used a health care claims database to identify patients with moderate to severe plaque psoriasis. Participants completed the Treatment Satisfaction Questionnaire for Medication. Results were compared between patients experienced with biologics (adalimumab, etanercept, or ustekinumab) or not (cyclosporine or methotrexate). Participants were asked for their choices of dosing options of once every 1–2 weeks, 3–4 weeks, 1–2 months, or 2–3 months. Participants were also asked for their choices of dosing options of every 1, 2, 3, and so on up to every 12+ weeks.Results: A total of 426 patients completed the survey (263 biologic-experienced and 163 biologic-naïve patients). Patient satisfaction with psoriasis treatment was significantly higher in the biologic-experienced cohort. The most frequently chosen option (38.8% of all participating patients) was every 2–3 months; 37.3% chose once every 1–2 weeks. Significant differences were found in the percentage of biologic-naïve patients choosing 2–3-month (49.7%) over 1–2-week (20.9%) dosing (P<0.001). Among biologic-experienced patients, the difference between the percentage of patients choosing the 2–3-month (35.7%) and 1–2-week (41.8%) options was not significant (P=0.264). The two most often week-specific intervals chosen by biologic-naïve patients were 12+ weeks (42.3%) and 4 weeks (15.6%). The biologic-experienced patients most often chose 12+ weeks (31.2%) and 1 week (25.9%).Conclusion: Patients using biologics reported satisfaction with their treatment, which may positively affect outcomes. Longer dosing intervals were chosen most frequently among all patients combined. Reports of patient satisfaction with prior treatments and choices regarding dosing frequency, among all other considerations, should be evaluated in determining an appropriate biologic medication for psoriasis. Keywords: psoriasis, biologic treatment, patient satisfaction, biologic dosing, patient choice